ANALISIS AKTIVITAS PERLINDUNGAN SINAR UV EKSTRAK ETANOL DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) BERDASARKAN NILAI SUN PROTECTION FACTOR - St. Maryam; Elka Praningsih; Andi Trihadi Kusuma (Fakultas Farmasi UMI, 2022)
UV rays have a negative impact on the skin, but can be minimized by using UV-protective ingredients. The leaves of Pandan Wangi (Pandanus amaryllifolius Roxb.). Contain alkaloid compounds, flavonoids, saponins, tanins, polyphenols which function as natural antioxidants. The purpose of study is determine the UV protection activity of the ethanol extract of fragrant pandan leaves. Based on the Sun Protection Factor (SPF) value using the UV- Vis Spectrophotometric method at wavelengths 290, 295, 300, 310, 315, 320 nm. The result showed that fragrant pandanus leaves (Pandanus amaryllifolius Roxb.) Had a minimum UV protection activity value of 3,8979 at a concentration of 1%, extra protection 6,2456 at a concentration of 3%, maximum protection of 9,4603 at a concentration of 5%.